Pharmacokinetic and pharmacodynamic modelling of the novel human granulocyte colony-stimulating factor derivative Maxy-G34 and pegfilgrastim in rats - Scholz, Markus; Engel, Christoph; Apt, D.; Sankar, S. L.; Goldstein, E.; Löffler, Markus (Cell proliferation, 2009)
OBJECTIVES\backslashr\backslashnThis study aims to compare pharmacokinetics and pharmacodynamics of pegfilgrastim, a pharmaceutical recombinant human granulocyte colony-stimulating factor (rhG-CSF), with that of a newly developed reagent, Maxy-G34. This comparison was performed using rat experiments and biomathematical modelling of granulopoiesis.\backslashr\backslashnMETHODS\backslashr\backslashnHealthy rats and those with cyclophosphamide-induced neutropenia were treated with either pegfilgrastim or Maxy-G34 under various schedules. Time courses of absolute neutrophil count (ANC) and G-CSF serum level were measured and we constructed a combined pharmacokinetic/pharmacodynamic model of both drugs. Neutropenic episodes were assessed by experimental data and model simulations.\backslashr\backslashnRESULTS\backslashr\backslashnBoth Pegfilgrastim and Maxy-G34 showed strong dose-dependent efficacy in reducing neutropenic episodes. However, time courses of ANC and G-CSF serum levels were markedly different. The biomathematical model showed good agreement with these data. We estimated that differences between the two drugs could be explained by lower bioavailability and reduced elimination of Maxy-G34. Based on the data and model interpolations, we estimated that Maxy-G34 is superior in reducing neutropenic episodes. Also, we predicted that G-CSF administration 48 h after cyclophosphamide would be superior to its administration after 2 or 24 h, for both derivatives.\backslashr\backslashnCONCLUSION\backslashr\backslashnMaxy-G34 is a highly potent drug for stimulation of neutrophil production in rats. By our modelling approach, we quantified differences between Maxy-G34 and pegfilgrastim, related to pharmacokinetic parameters. Model simulations can be used to estimate optimal dosing and timing options in the present preclinical rat model.